THE EFFECT OF SIZING COMPOUND ON THE ELECTROPOLYMERIZATION OF PYRROLE AND THE IMPEDANCE OF CARBON FIBER COATED WITH POLY(PYRROLE) - Hacer DOLAS (Journal of the Turkish Chemical Society, Section A: Chemistry, 2016)
Carbon Fiber (CF) is used as strengthening material in resin composites having high performance in most industrial area due to that it has mechanical properties such as low weight, high durability and toughness. The mechanical performances of composite materials depend on the features of fiber and matrix which composed them. The one of methods which improves the features of fiber surface is the coating on fiber surface with thin film.As coated fiber with electropolymer, as increased the mechanical durability of the composite. In this study, carbon fibers were coated with Polypyrrole (PPy) in presence of sizing compound (SC) based on epoxy, electrochemically. During process, it was investigated how current, obtained coating weights and impedance data, especially capacitance, changed by the amount of SC. For this reason, different amount of SC (%0; % 0.18; %1.8 v/v) was added into the electrolyte solution (0.1 M NaClO4-ACN) including 0.1 M Pyrrole (Py).Coating process was carried out by using Constant Potential or Cyclic Voltammetry Techniques. Other techniques for investigations were gravimetrical analysis, electrochemical impedance spectroscopy, Fourier Transform Infrared Spectroscopy (FT-IR) and Light Microscopy. In end of the coating the weight of coating and specific capacitance (Csp) values were0.8 mg/g and 114 µF for % 0 of SC 10 mg/g and 57 µF for %0.18 of SC and 1.73 mg/g and 166 µF for %1.8 of SC, respectively. As a result, the coating weight and capacitance data (especially, Csp,) of carbon fiber coated with PPywas changed with the amount of SC added into electrolyte, inversely.